Effects of Venezuelan migration on Colombian price level (2021)
This study evaluates the causal impact of the Venezuelan migration on the price level of goods and services in Colombian host cities. The inflow of migrants to a city have a demand shock through an increase in consumption levels, and a supply shock through a decrease in the production costs. I use an Enclave instrumental variable strategy, which exploits the tendency of migrants to settle in places with previous migrant networks. I find that the Venezuelan migration increases averages prices in the non-tradable sector and has no effect on the price of food, tradable goods, transport and energy sectors. I provide evidence that this result may be related to the effect migration has on the price of education and housing. My estimates suggests that a 1 percentage point increase in the migration rate is associated with an 0.913% average increase in the price of the nontradables. This result is consistent with a demand side shock.